Effects of stress on foliar trichomes plasticity in Mentha piperita - MEHERI ASKARY; SEYED MEHDI TALEBI; FARIBA AMINI; ALI DOSTI BALOUT BANGAN (Nusantara Bioscience, 2016)
Abstract. Askary M, Talebi SM, Amini F, Bangan ADB. 2016. Effects of stress on foliar trichomes plasticity in Mentha piperita. Nusantara Bioscience 8: 32-38. Mentha piperita is considered as the most economically important aromatic as well as medicinal herb of Labiatae family. This medicinal herb has traditionally been used to treat a variety of digestive complaints. In the present study, effects of twenty treatments of salt and nanoparticles of Iron oxide were examined on the leaf trichomes morphology of M. piperita samples. In total twenty solutions, combinations of four salt concentrations with five iron oxide nanoparticles concentrations were used for the treatments. Different kinds of glandular and non-glandular trichomes were found in the studied plant samples. Glandular trichomes were seen in the shapes of peltate, short-stalked capitate and non-stalked and non-glandular ones were unbranched and had one to seven cells. The obtained results showed that the kind and abundant of trichomes differed between the studied treatments. Statistical analyses showed significant positive correlations between salt concentrations with trichomes density. While, negative significant correlations have occurred between concentrations of nanoparticle of iron oxide with some kinds of trichomes.